The Upper-Silesian conurbation on the path towards the “Silesia” metropolis - Szajnowska-Wysocka, Alicja; Zuzańska-Żyśko, Elżbieta (Bulletin of Geography. Socio-economic Series, 2013)
In its methodological context, the article, expands on the idea of the organization of the “Silesia” superstructure. The idea of establishing a common urban organism emerged with the local governments of the Upper Silesian conurbation cities and was dictated by the need to find a way to change the traditional image of the Silesian region and its post-industrial role in the economic space of the country, as well as Europe. Therefore, in 2009, the Metropolitan Association of Upper- Silesia, an association for the initial institutionalization of “Silesia”, was registered, because “Silesia” does not hold any administrative or legal force. Such an organizational “revolution” of the Upper Silesian conurbation initiated a wide social debate, in which the arguments of both supporters and opponents of such an enterprise in the Silesian region became apparent, together with misunderstandings related to the term “metropolis”, and the idea of establishing “Silesia”. Representatives of local governments chose the more prestigious term “metropolis” as if a complex metropolisation had taken place in the Upper Silesian conurbation. It would be adequate, however, to look only for the first features of metropolitan functions in this de-industrialized and restructured region, which are going to shape the longlasting metropolisation process under the influence of globalisation.